Extension and advisory services role in the COVID-19 crisis - Davis, Kristin E.; Chen, Kevin Z.; Leclair, Mark; Karamidehkordi, Esmail; Larsen, Carl; Babu, Suresh Chandra (United States Agency for International Development, 2020)
There is increasing concern that the COVID-19 pandemic will have dire consequences for food security unless adequate safeguards are established. Food supply chains must continue to function; the health of food system workers must be protected; and measures to ease the economic blow from lost incomes must be taken. Information, advice, and coaching for rural establishments––such as trusted rural communication and education institutions––are a critical piece of emergency response to such a crisis, providing credible information about the virus and farming advice to adapt to various shocks.